Small states in multilateral economic negotiations (Routledge, 2014)
This text addresses the puzzle, Can David take on Goliath in multilateral economic negotiations, and if so, then under what conditions? It offers new insights into the vulnerabilities that small states face in multilateral economic negotiations, and also mechanisms whereby these weaknesses might be overcome and even used as an advantage.